Middle School Students’ Sustainable Living Awareness and Conscious Consumerism Perceptions: A Prediction Study (Journal of Science Learning, 2026)
The purpose of this study is to examine whether middle school students' awareness of sustainable living predicts their perceptions of conscious consumerism. A predictive correlational design was employed. The sample was selected using convenience and criterion sampling methods. One hundred fifty-two middle school students (seventh and eighth grade) participated in the study. The participants included 97 females and 55 males from an urban public middle school in Kahramanmaraş, representing a predominantly middle-income socioeconomic background. Data were collected using two instruments: the Sustainable Living Awareness Scale (environmental, economic, and social dimensions) and the Conscious Consumerism Perception Scale (consumer responsibility, quality awareness, and budget–price consciousness). Data were analyzed using simple linear regression. The results indicate that middle school students' awareness of sustainable living significantly predicts their perceptions of conscious consumerism. This findings that enhancing students' awareness of sustainability is associated with an increased perception of conscious consumerism. Future research could explore the impact of activities designed to raise students' awareness of sustainable living on their perceptions of conscious consumerism through experimental methods.